Oxymatrine Inhibits Twist-Mediated Renal Tubulointerstitial Fibrosis by Upregulating Id2 Expression - Xiao, Ying; Peng, Can; Xiao, Yawen; Liang, Dan; Yuan, Zhiping; Li, Zhiyang; Shi, Mingjun; Wang, Yuanyuan; Zhang, Fan; Guo, Bing (Frontiers in Physiology, 2020)
The final pathway for the development of diabetic nephropathy (DN) into chronic renal failure in DN is glomerulosclerosis and tubulointerstitial fibrosis. Renal tubular lesions can occur in the early stage of DN renal injury. Cumulative evidence shows that oxymatrine (OMT) has a variety of biological and pharmacological properties. In recent years, more attention has been paid on the preventive and therapeutic influence of OMT on organ fibrosis. In this experiment, db/db mice were intraperitoneally injected with OMT 120 mg/ kg for eight weeks, and NRK-52E cultured with 30 mmol/L glucose and 0.1 mg/mL OMT for 48-h. We investigated the relationship between Id2 and Twist in NRK-52E cells and the effect of OMT on the expression of E-cadherin, α-SMA, Fibronectin, and Collagen-Ⅳ by Western blot, Real-time PCR, Immunofluorescence, cell transfection, Co-Immunoprecipitation, and Luciferase assays. OMT increased the expression of Id2 but decreased that of Twist under high glucose condition in vitro and in vivo. The promoted recovery of Id2 facilitated its binding to Twist and affected E-cadherin activity inhibiting EMT and the excessive proliferation and abnormal deposition of ECM. In brief, OMT promotes Id2 to reverse EMT and exert antifibrotic effect in diabetic renal tubular epithelial cells by binding Id2 to Twist and affecting its transcriptional activation of downstream target genes. Or findings provide a new experimental basis for delaying the progress and for treatment of diabetic renal fibrosis.